Kritik Atas Sunah Sebagai Bagian TafsÄ«r bi al-Maâ€™sÅ«r: Menyoal Otoritas Sunah Sebagai Acuan Penafsiran dalam TafsÄ«r Al-JalÄlain - M Miski (IAIN Pekalongan, 2017)
TafsÄ«r al-JalÄlai, like TafsÄ«ral-Maá¸¥allÄ« andas-SuyÅ«á¹Ä«, has not been created from a vacuum, but from a specific context of social reality which is laden with certain ideologies. The questionsthat follow then are how al-Maá¸¥allÄ« and as-SuyÅ«á¹Ä«have put their own ideological genre into TafsÄ«r al-JalÄlain when interpreting al-Qurâ€™an and how this ideological preference in turn brings about theoretical implications for tafsÄ«r bi al-maâ€™sÅ«r? This paper adopts the perspective of constructionism and that of literature study. The primary data were TafsÄ«r al-JalÄlain, which were analysed by means of intertextuality. The main findings revealed that Sunah in the TafsÄ«r al-JalÄlain have been selected and sorted out in accordance with an ideological genre of Syafii. Building on these observations, we concluded that the existence of SunahNabi which are part of tafsÄ«r bi al-maâ€˜á¹¡Å«r (an-Naql), despite being hailed as the most authoritative interpretation of al-Qurâ€™an, tends to be biased and, therefore, its generalizability should be interpreted with caution. We suggested that there should be a more specific terminology in between al-Qurâ€™an that is interpreted by Nabi himself (i.e., at-TafsÄ«r an-NabawÄ«), which tends to be neutral, andÂ al-Qurâ€™an that is interpreted by scholars through the lens of SunahNabi (at-TafsÄ«r bi as-Sunnah an-Nabawiyyah), which is undoubtedlyvulnerable to the interest of these scholars